Highlights of the 1st Argentine Symposium of Young Bioinformatics Researchers (1SAJIB) organized by the ISCB RSG-Argentina - Parra, Rodrigo Gonzalo (2016)
The 1st Argentine Symposium of Young Bioinformatics Researchers took place on 9-10 May 2016 at Universidad de Buenos Aires, Buenos Aires, Argentina. This event evolved from a previous meeting series known as Argentine Student Council Symposium that have been successfully organized since 2012 by the Regional Student Group of Argentina (RSG-Argentina). The change in name reflects the new vision of the organizing committee to gather together all students at Bachelor, Master and PhD levels, postdocs and researchers that are still not Principal Investigator. Here we summarize the main activities and outcomes from this year’s meeting and offer some insights into our future plans.